Διαδικτυακή πλατφόρμα για εξ' αποστάσεως υποστήριξη ασθενών και ηλικιωμένων με χρήση Raspberry - Κορρές, Σταμάτιος - Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2017)
The need of high level medical care is very crucial for people. Although the progress of medicine is rapid the last decades, the problem of sufficient and efficient health care still remains. The social groups that have the most difficulty accessing those services are the elderly, those who live at remotes areas or islands and also those who have lower incomes. The development of Telecommunications and Computer Science can offer a very drastic solution to the above problems. Their main application is Telehealth. Telehealth is able to provide accessibility, which is independent of the geographic distances, significantly reduces the communication time, contributes to punctual prevention and confrontation of emergency situations through constant and remote monitoring and also is very cost-efficient. The scope of this thesis is the design and implementation of a web based platform which provides remote monitoring of health records and biosignals, projection of those biosignals in interactive diagrams, wireless and automated biosignals storage, reminders for activities or/and medication and also an integrated social network which eases the user’s real-time communication, allowing not only video calls but also written text. The patients of the platform will access it through a Raspberry Pi, which is a complete portable computer equipped with the necessary peripherals. Great emphasis was put on the ease of use, so no previous knowledge is required from users. Regarding the technology used, the Servers of the system are implemented with Nodejs, the database used is mongoDb and AngularJS was deployed as the front-end framework.